2013
DOI: 10.1161/circulationaha.112.000024
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 4–Dependent Microglial Activation Mediates Spinal Cord Ischemia–Reperfusion Injury

Abstract: Background— Paraplegia continues to complicate thoracoabdominal aortic interventions. The elusive mechanism of spinal cord ischemia–reperfusion injury has delayed the development of pharmacological adjuncts. Microglia, the resident macrophages of the central nervous system, can have pathological responses after a variety of insults. This can occur through toll-like receptor 4 (TLR-4) in stroke models. We hypothesize that spinal cord ischemia–reperfusion injury after aortic occlusion results from TL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
71
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 26 publications
4
71
0
Order By: Relevance
“…It was also found that TLR4‐dependent microglial activation mediates spinal cord ischemia–reperfusion injury 11. TLR3 and TLR4 share a common signaling pathway via TRIF17; therefore, we sought to elucidate whether TLR4 was also stimulated by shock waves.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also found that TLR4‐dependent microglial activation mediates spinal cord ischemia–reperfusion injury 11. TLR3 and TLR4 share a common signaling pathway via TRIF17; therefore, we sought to elucidate whether TLR4 was also stimulated by shock waves.…”
Section: Resultsmentioning
confidence: 99%
“…Besides acute paraplegia directly after surgery, delayed‐onset paraplegia has been observed 10. Toll‐like receptor (TLR) 4–dependent microglial activation has been identified in this setting to mediate spinal cord ischemia–reperfusion injury 11. Microglia are spinal resident macrophages and the main cell type in the resting central nervous system that expresses TLR3 and TLR4 12, 13.…”
mentioning
confidence: 99%
“…Few of the shortcomings include lack of an anatomically clear ischemic penumbra, which is the target of many neuroprotective drugs, and the absence of reperfusion. It is well known that reperfusion following ischemia is characterized by changes like increased production of reactive oxygen species, infiltration of inflammatory cells and increased cytokine production [30][31][32] . Lack of reperfusion in PT means the changes associated with reperfusion injury in SC will remain difficult to study using this model.…”
Section: Discussionmentioning
confidence: 99%
“…The neural tissue is very susceptible to oxidative damage, due to its high oxygen requirement (up to 20% of the total oxygen intake, even though it is 2% of the total body weight) and its low antioxidant activity with respect to other tissues (8). Nevertheless, IRI in the spinal cord is also caused by microglial activation as well as blood spinal cord barrier disruption (9,10). Thus, a promising therapeutic approach to CSM has to target multiple mechanisms of injury.…”
mentioning
confidence: 99%